Effect of Iranian Propolis on Salivary Total Antioxidant Capacity in Gamma-irradiated Rats - Aghel, Sara (J Dent Res Dent Clin Dent Prospects, 2014)
Background and aims. The antioxidant and anti-inflammatory properties of propolis were studied. Since saliva containsantioxidants and radiotherapy of the head and neck mainly affects the saliva, salivary antioxidant defensive mechanism iscompromised with oxidative stress produced by radiation therapy. Therefore, the aim of the present study was to investigatethe effect of propolis on salivary total antioxidant capacity in irradiated rats. Materials and methods. The study was conducted on 28 rats, 7-11 weeks of age (160±20 g), divided into four groups:saline with no radiation (S), saline and radiation (SR), propolis with no radiation (P) [400 mg/kg IP], propolis and radiation(PR) [400 mg/kg IP]. SP and PR were exposed to 15 Gy of gamma irradiation for 7 minutes and 39 seconds. The rats received intraperitoneal injections each day for 10 days, and their tongues and lips were daily examined for mucositis; salivasample were also taken three times on days 0, 6, and 10. Results. Mucositis incidence appeared to be delayed in the PR compared to the SR, and the severity was significantlyhigher in the SR compared to the PR. No significant alterations were observed in salivary antioxidant levels during the ex-periment, except the SR group in which a significant reduction was found. Conclusion. Propolis might reduce and delay radiation-induced mucositis in animal models; it might be able to prevent thereduction in salivary antioxidant levels in irradiated rats as well.